Penerapan Pendekatan “Beyond Calories”: Rehabilitasi Nutrisi pada Kasus Gizi Buruk Berat dengan Komorbiditas Kompleks - Maria Devi; Arief Rahman (Medula, 2026)
Severe acute malnutrition in children with congenital and chronic comorbidities presents a significant challenge in both diagnosis and management. Children with Down syndrome have increased nutritional requirements and are more susceptible to gastrointestinal disturbances; therefore, nutritional strategies should extend beyond merely meeting caloric demands and should consider the patient’s nutritional tolerance and absorptive capacity. This case report describes a 12-month-old male infant with Down syndrome, a history of multiple surgical interventions for anorectal malformation (anal atresia), a cow’s milk protein allergy, and hypothyroidism, who presented with chronic diarrhea, failure to thrive, and severe wasting. Anthropometric assessment revealed a body weight of 4.2 kg, a body length of 62 cm, and a mid-upper arm circumference of 6.5 cm, consistent with a diagnosis of marasmic severe acute malnutrition according to WHO criteria. Nutritional rehabilitation was initiated using an amino acid based elemental formula, intravenous fluid therapy, empirical antibiotic treatment (cefotaxime), zinc supplementation, and levothyroxine. Clinical improvement was observed during the initial stabilization phase; however, progression into the rehabilitation phase was complicated by oral feeding intolerance, recurrent vomiting, and persistent diarrhea, necessitating reassessment of the nutritional management strategy and close monitoring for formula intolerance. The use of an elemental formula contributed to overcoming challenges related to nutrient absorption and immunological tolerance in this patient. This case highlights the importance of a comprehensive, individualized, and multidisciplinary nutritional approach, accompanied by family education and intensive clinical monitoring to support successful long-term recovery.